Effectiveness of Training Variations in Improving Forehand Smash Ability in Badminton Game - Kuswanti, Nikmah; Mushofi, Yuskhil; Kurniawan, Rubbi; Setyawan, Trinovandhi; Windriyani, Shinta Masitho (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aims to investigate the effectiveness of variations of arm muscle strength training and body flexibility in improving the forehand smash hitting ability of badminton players. Materials and methods. The research sample consisted of 14 badminton players who were members of PB Nusantara Malang. The research used a quasi-experimental method with the research design used in the form of a one group pretest-posttest design. The research instrument used a forehand smash test. Results. The average result of forehand smash before treatment was 17.286 ± 6.787, and after treatment the average value was 19.571 ± 6.047. Data analysis using the Paired Sample T Test level of significance level of 0.00. This means that there is a significant difference between posttest and pretest. Conclusion. Based on the results of the research that has been done, it can be concluded that training variations of arm muscle strength training and body flexibility training is an effective combination of exercises to improve the results of forehand smash shots in badminton games. This can be used as the basis for trainers in compiling badminton training programmes in order to get maximum results, especially in forehand smash training.